SPE Reservoir Simulation Symposium 2015
DOI: 10.2118/ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling from Reservoir to Export: A Compositional Approach for Integrated Asset Model of Different Gas Fields in North Kuwait Jurassic Carbonate Reservoirs

Abstract: Shale and tight gas reservoirs consist of porous structures with pore diameter in the range of some mm to m. At these scales, the pore diameter becomes comparable to the gas mean free path. Flows in these structures fail often in the transition and slip regimes. Standard continuum fluid methods such as the Navier-Stokes-Fourrier set of equations fail to describe flows of these regimes. We present a Direct Simulation Monte Carlo study of a 3D porous structure in an unlimited parallel simulation. The three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…which is based on variable flow head model and showed that it has advantages over the previous studies. Christou and Kokou Dadzie [17] have recently used this model in their study of direct simulation Monte Carlo methods in porous media with varying Knudsen number. The equation for the mean free path is given by,…”
Section: Classifications Of Flow Regimes Based On Knudsen Numbermentioning
confidence: 99%
“…which is based on variable flow head model and showed that it has advantages over the previous studies. Christou and Kokou Dadzie [17] have recently used this model in their study of direct simulation Monte Carlo methods in porous media with varying Knudsen number. The equation for the mean free path is given by,…”
Section: Classifications Of Flow Regimes Based On Knudsen Numbermentioning
confidence: 99%
“…Torrens et al (2015) also discussed an onshore fractured carbonate gas condensate and volatile oil asset in Northern Kuwait. The integrated model is implemented to design new well drilling and surface facilities.…”
Section: Introductionmentioning
confidence: 99%